IMPLEMENTASI KURIKULUM PENDIDIKAN 2013 PADA SEKOLAH DASAR DI KABUPATEN REJANG LEBONG - Resmani, Meli (Jurnal Governance dan Administrasi Publik, 2017)
This study aims to determine the implementation of the 2013 Education Curriculum at Elementary Schools in Rejang Lebong Regency, and to find factors that hinder the implementation of the 2013 Education Curriculum in that district. This research uses methods qualitative. Informants in this study are competent people who know the problem under study. The informants in this study included 2 Public Elementary School Principals, 2 Private SD Principals. 2 Public Elementary School Teachers, 2 Private Elementary School Teachers and 2 Rejang Lebong District Education Officers. The technique of taking informants in the study used purposive sampling method. Data analysis in this model consists of four interacting components, namely data collection, data reduction, data presentation and drawing conclusions and verification. The results showed that the implementation of the 2013 curriculum at Elementary Schools in Rejang Lebong Regency has not been maximized due to lack of facilities and infrastructure , insufficient budget, and low teacher competence.